PSIKOEDUKASI UNTUK MENINGKATKAN SELF-EFFICACY PADA ANGGOTA KOMUNITAS FUTSAL “OR” DI KOTA S LATAR LAYANAN KOMUNITAS - Ghazi Dzar Al Ghifari Ahda; Amanda Pasca Rini (Jurnal Riset Multidisiplin Edukasi, 2025)
Futsal performance requires not only physical and technical skills but also strong psychological readiness, particularly in competitive situations. One of the key psychological factors influencing athletic performance is self-efficacy, defined as an individual’s belief in their ability to organize and execute actions necessary to achieve desired outcomes. This article aims to describe the implementation of psychoeducation as a psychological intervention to enhance self-efficacy among members of the “OR” Futsal Community in City S within a community service context. The study employed a qualitative descriptive approach with a community-based service design, involving 10 core players aged 19–23 years and one coach as a key informant. Data were collected through observation, semi-structured interviews, Focus Group Discussions (FGD), and self-efficacy pre-test and post-test measures. The assessment results indicated a significant decline in players’ self-efficacy during official competitions compared to training sessions, manifested through decision-making hesitation, emotional regulation difficulties, and weakened intragroup communication. The two-day psychoeducational intervention demonstrated positive outcomes, including increased self-efficacy, greater self-awareness, improved initiative-taking, and more supportive team communication. These findings suggest that self-efficacy psychoeducation is a relevant and effective approach to strengthening mental readiness and team performance in competitive futsal contexts.